Pak-India Trade Relationship Based on Gravity Modeling: Issues and Challenges - Abidi, Asad Raza; Halepoto, Ali Hassan; Chandio, Fayyaz Raza; Shaikh, F. M (Journal of Asian Business Strategy, 2013)
This research explores the Pak-India Trade reforms and its impact on the economy of Pakistan. Economic integration is considered as a policy by which trade barriers should fall gradually or disappear fully among members of a trading block. The regional Block trade is gaining importance in the world to make economic cooperation more beneficial to the members in order to deepen their economic relations. In the current scenario the trade expansion and implementation of block trade between Pakistan in India. The data were collected from various secondary sources and data were analyzing by using GEN-STAT- software. It was revealed that Pakistan getting benefit on Trade with India in agriculture trade. Results of this study indicate that positive economic circumstances attract developing trade flows between Pakistan and selected blocs.